2014
DOI: 10.1016/j.immuni.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Restricted Interleukin-10 Receptor Deficiency, but Not IL-10 Deficiency, Causes Severe Spontaneous Colitis

Abstract: Interleukin-10 (IL-10) is a pleiotropic anti-inflammatory cytokine produced and sensed by most hematopoietic cells. Genome-wide association studies and experimental animal models point at a central role of the IL-10 axis in inflammatory bowel diseases. Here we investigated the importance of intestinal macrophage production of IL-10 and their IL-10 exposure, as well as the existence of an IL-10-based autocrine regulatory loop in the gut. Specifically, we generated mice harboring IL-10 or IL-10 receptor (IL-10Rα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
434
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(484 citation statements)
references
References 67 publications
31
434
1
5
Order By: Relevance
“…However, IL-10 suppresses immunity when IL-10 binds to IL-10Rs 31,34,35,44 . IL-10R expression on HA-specific CD4 þ T cells remains at the base level in the early phase of our model of influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, IL-10 suppresses immunity when IL-10 binds to IL-10Rs 31,34,35,44 . IL-10R expression on HA-specific CD4 þ T cells remains at the base level in the early phase of our model of influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…31). IL-10R1 induction upregulates IL-10R expression, which is essential for IL-10-mediated suppression 31,34,35 . Ding et al 44 demonstrated how IL-10R expression has a critical role in determining whether cells respond to IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…134 Production of GM-CSF and VEGF-C during inflammation may reprogramme the differentiation of monocytes into m that produce reparative mediators such as arginase, prostaglandins and IL-13. 200,201 Thus the overall role of the monocyte-m lineage in intestinal inflammation may reflect a balance between local pathogenic and regulatory mechanisms.…”
Section: Macrophages In Intestinal Inflammationmentioning
confidence: 99%
“…On the other hand, macrophages that are located deeper in the gut wall efficiently eradicate microbes that breach the intestinal epithelial barrier without mounting a potent inflammatory response. This phenotypic difference is orchestrated by interleukin-10 (IL-10), which is secreted locally by T cells, B cells, dendritic cells, and some epithelial cells to limit inflammatory responses [33,34]. The gene regulatory mechanisms controlling this behavior have been recently examined, revealing that the chromatin accessibility landscape of IL-10 knockout intestinal macrophages was similar to that of inflammatory macrophages.…”
Section: The Temporal and Spatial Properties Of Macrophage Regulatorymentioning
confidence: 99%